Association Between Experimental Pain Biomarkers and Serologic Markers in Patients With Different Degrees of Painful Knee Osteoarthritis. Issue 12 (December 2014) - Arendt‐Nielsen, Lars; Eskehave, Thomas N.; Egsgaard, Line L.; Petersen, Kristian K.; Graven‐Nielsen, Thomas; Hoeck, Hans C.; Simonsen, Ole; Siebuhr, Anne S.; Karsdal, Morten; Bay‐Jensen, Anne C.
<x xml:space="preserve">Abstract</x> Objective To assess the association between pain mechanisms (sensitization) and biochemical markers for cartilage, bone, and inflammation in patients with knee pain. Methods The study group comprised 281 patients with different degrees of knee pain intensity and radiographic findings (using the Kellgren/Lawrence [K/L] scale). The following structurally related serologic biomarkers were measured in serum: high‐sensitivity C‐reactive protein (hsCRP), matrix metalloproteinase (MMP)–mediated breakdown of CRP (CRPM), MMP‐mediated degradation of type I collagen (C1M), C2M, and C3M. Pressure–pain thresholds (PPT) (peripheral and spreading sensitization), temporal summation of pain, and conditioning pain modulation (CPM) (with the latter 2 biomarkers representing generalized sensitization) were assessed. For each pain parameter, the patients were categorized as most sensitized or least sensitized. Results Correlations were observed between the pain biomarkers PPT, temporal summation, and CPM and maximal pain intensity during the last 24 hours. Significant associations between most of the serologic biomarkers were observed. A high CRPM level was associated with centralized sensitization (temporal summation and CPM). None of the serologic markers correlated with the intensity or duration of knee pain, and only hsCRP correlated with the K/L grade. The most‐sensitized group contained more women than men, and the least‐sensitized group contained more men than women. Conclusion A platform of mechanistic pain biomarkers in combination with structure‐related serologic biomarkers provides new possibilities for understanding how osteoarthritis‐related structural features may be associated with pain and pain sensitization. This study showed significant correlations between central pain sensitization and CRPM as a possible measure for chronic inflammation. Future pain association studies should include biomarkers representing the local joint environment more specifically.